Implementasi Barisan dan Deret dalam Ilmu Ekonomi - Dyah Permata Hayuningtyas; Febita Miranda Witri; Risna Fradila Octaviani; Dedek Kustiawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study discusses the implementation of sequences and series in economics. The research method used in this study is a qualitative method. The data collection technique used in this study was a literature study. A sequence is an arrangement of numbers formed according to a certain order. Sequences and series consist of two parts each, namely arithmetic sequences and geometric sequences as well as arithmetic series and geometric series. In economics the concepts of arithmetic lines and series are used for matters relating to calculations such as the calculation of capital, interest rates, installments, and the number of interest periods on a single interest basis. In economics the concept of geometric lines and series is usually used in calculating the final capital, interest rates, and the number of loan periods on a compound interest basis. The concepts of sequences and series are also related to Malthus' theory of population growth.